PROSEDUR PERMOHONAN SHAR-E CARD PADABANK MUAMALAT - Aprilianti Aprilianti (Universitas Lampung, 2007)
After the economic crisis that followed the liquidation of some national private banks in 1997 gave rise to alternative thinking and measures to develop banking activity based on Islamic principles. Islamic principles reflected in the pattern of bamk operating in accordance with Islamic principles, especially regarding the procedures for bermuamalah in Islam. Shar-E Card is one type of credit card services by a bank Muamalat where the balance is outstanding amounts dengam mudaraba principle that no restriction for banks to use the funds raised, bamk shall memberitahukam to the owner of the funds of the ratios and procedures for the provision of benefits and or the calculation of benefit sharing as well as risks that may arise from the storage of funds. Keywords: Shar-E Card, Bank Muamalat